상용전자부품을 이용한 직관적이고 경제적인 바이오센싱 플랫폼의 개발 - Han Yong Duk (The Graduate School, Ajou University, 2015)
The commercialized common electronics components were reassembled and utilized for the materialization of cost-effective and user-friendly biosensing platform. 1. For the accurate boronate-based biosensing of glycated hemoglobin (HbA1c) in whole blood, commercial hard-disk drive (HDD)-mediated hemoglobin separation system was developed. By using the developed hemoglobin separator, hemoglobin was isolated with high purity from the whole blood sample containing glycosylated biomolecules which can be a signal interference in the boronic acid-based HbA1c detection. Based on the developed sample preparation technique and boronic acid-mediated electrochemical affinity biosensing method, HbA1c in whole blood was quantified linearly within a range of 4.5% to 15% from the separated hemoglobin samples (HbA1c/total hemoglobin). 2. By reassembling common office supplies, an intuitive optical biosensing system was developed. A laser pointer and the solar cell from a calculator were utilized in the developed optical biosensing system as the light source and signal transducer, respectively. For intuitive signal evaluation, a multimeter was used. The two types of conventional enzymatic colorimetric assays using peroxidase were employed with the optical biosensing system. In this system, the optical biosensing signals from the colorimetric assays are appeared as changes in DC voltages on the multimeter. By using the developed optical biosensor, the glucose and protein biomarker (urinary cross-linked C-telopeptide of type II collagen; uCTX-II) were quantitatively analyzed. With glucose, the voltages registered were linearly correlated with the glucose concentration, from 0 to 10 mM. Using a competitive immunoassay for uCTX-II, the system exhibited a calibration curve with a dynamic detection range between 1.3 and 10 ng/mL uCTX-II. 3. The applicability of previously developed optical transducing system employing common electronics components to the nanoparticle-based optical analysis was demonstrated. For the diverse application, a light source module containing two different laser diodes (532 nm laser and 635 nm) were newly fabricated and adapted to the optical transducer comprising multimeter and solar cell. As a model nanoparticle, two types gold nanoparticle including spherical gold nanoparticle (GNP) exhibiting maximum absorbance at 526 nm and gold nanorod (GNR) exhibiting maximum absorbance at 624 nm were prepared and utilized as an optical signaling probe. By matching the emission spectra of lasers and absorption spectra of nanoparticles, DC voltage-based signals could be registered. For the assessment of our system to immunosensing, as model immunoreaction pairs, anti-mouse IgG/mouse IgG pair and anti-human IgG/human IgG pair were employed. To the superparamagnetic microparticles (MPs), anti-mouse IgG and anti-human IgG were modified as a capturing antibody. To the GNPs and GNRs, mouse IgG and human IgG were conjugated as an antigen, respectively. As a result, the concentration of GNPs and GNRs were changes in accordance with the amount of their corresponding MPs via immunoaffinity reaction on the developed optical transducing system. Based on these findings, we propose new biosensing platform technology based on the reassembling of common electronics components which can be adapted to various applications.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2015. 2
Keywords: 바이오센싱